Queering the late imperial Chinese Zhiguai tales: strange encounters in the non/human realm - Whyke, Thomas W. (2018)
This thesis uses critical theory to examine animal–human relationships in the zhiguai tales [志怪小说], using Deleuze and Guattari as the theoretical framework alongside which I draw on aspects of queer theory and animal studies to think through several intersecting ‘othernesses,’ including the ‘queer,’ the ‘animal,’ and the ‘strange.’ Zhiguai is a well-known transliteration for “Tales of the Strange,” a genre of writing featuring ghosts, magical animal–human shapeshiftings, dreams that intervene in reality, and other supernatural characters and events. In this thesis, the strange comes to the forefront in the figure of the non/human – a two-fold figure made up of both ‘human’ and ‘animal.’ Throughout this thesis I appropriate the term ‘queerkind’ to foreground this ‘strange’ figure, which cannot be wholly generalized as ‘the animal,’ but is instead a magical creature most often existing between ‘human’ and ‘animal.’